A new understanding of the history of limited liability: an invitation for theoretical reframing. Issue 5 (October 2020) - Harris, Ron
Abstract: I investigate the historical development of limited liability – widely considered a cornerstone of the business corporation – and challenge the commonplace linear narratives about how limited liability evolved. I dismiss the claim that limited liability was invented with the very first joint-stock business corporations around 1600. I also reject the assertion that it became dominant with the limited liability acts of the mid-19th century. My argument is that it was only around 1800 that limited liability became a separate corporate attribute, distinct from legal personality, and that limited liability in the modern sense became a uniform attribute of all corporations only in the 20th century. Since corporations, stock markets and the corporate economy enjoyed a long and prosperous history well before limited liability in its modern sense became established and dominant, the economic theory of limited liability needs to be revisited. The paper opens a new set of conceptual, empirical and theoretical research questions, and points to new possibilities in terms of viable future liability regimes.